2022
DOI: 10.1136/bmjopen-2021-056101
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram for the prediction of in-hospital mortality in patients with acute ST-elevation myocardial infarction after primary percutaneous coronary intervention: a multicentre, retrospective, observational study in Hebei province, China

Abstract: ObjectivesTo establish a clinical prognostic nomogram for predicting in-hospital mortality after primary percutaneous coronary intervention (PCI) among patients with ST-elevation myocardial infarction (STEMI).DesignRetrospective, multicentre, observational study.SettingThirty-nine hospitals in Hebei province.ParticipantsPatients with STEMI who underwent PCI from January 2018 to December 2019.InterventionsA multivariable logistic regression model was used to identify the factors associated with in-hospital mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Three studies exhibited a high risk of bias due to the use of multicentre data for retrospective analysis 16 20 22 ; 5 prospective cohort studies were deemed to show a low risk of bias as they inherently employed blinding 9 10 29 30 33 ; and the remaining 20 studies were identified with an unclear risk of bias as they did not report the methods used to measure or assess the predictors.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies exhibited a high risk of bias due to the use of multicentre data for retrospective analysis 16 20 22 ; 5 prospective cohort studies were deemed to show a low risk of bias as they inherently employed blinding 9 10 29 30 33 ; and the remaining 20 studies were identified with an unclear risk of bias as they did not report the methods used to measure or assess the predictors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has linked the clinical profile of ACS patients at admission to prognosis, with age, cardiac insufficiency, and blood pressure clinically recognized as independent markers of poor prognosis following PCI in ACS patients (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is linked to many cardiovascular diseases, including stroke [ 158 ], venous thromboembolic disease [ 112 ], pulmonary embolism [ 113 ], HF [ 114 ], and arrhythmias, especially sudden cardiac death (SCD) [ 116 ] and atrial fibrillation (AF) [ 117 ]. Furthermore, it causes specific issues in key topics for cardiologic patient management, such as differences in specificity and sensitivity in non-invasive and invasive diagnostic tools [ 159 ], changes in platelet reactivity [ 160 , 161 ], a different short- and long-term outcome after percutaneous coronary intervention PCI [ 162 164 ] or cardiac surgery [ 159 ].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%